Differential effects of prenatal psychological distress and positive mental health on offspring socioemotional development from infancy to adolescence: a meta-analysis - Phua, Desiree Y.; Chew, Chermaine S. M.; Tan, Yang Lik; Ng, Benjamin J. K.; Lee, Florence K. L.; Tham, Megan M. Y. (Frontiers in Pediatrics, 2023)
The impact of prenatal maternal mental health on offspring socioemotional development is substantial and enduring. Existing literature primarily focuses on the effects of psychological distress during pregnancy, emphasizing adverse child outcomes. Recent studies, however, highlight the unique impact of positive maternal mental health on child outcomes. To elucidate the differential associations of maternal psychological distress and positive mental health during pregnancy with child outcomes, we conducted a systematic literature search and random-effects meta-analyses on studies investigating the associations of prenatal maternal mental health with child socioemotional development. Our analyses, comprising 74 studies with 321,966 mother-child dyads across 21 countries, revealed significant associations of prenatal psychological distress with both adverse and positive child socioemotional outcomes. Notably, the effect sizes for the association of psychological distress with positive child outcomes were smaller compared to adverse outcomes. Positive prenatal mental health, on the other hand, was significantly associated with positive socioemotional outcomes but not adverse outcomes. This meta-analysis highlights the independence of negative and positive prenatal mental health constructs and their distinct relationships with child socioemotional development. The findings underscore the importance of considering the positive spectrum of maternal mental health and developmental outcomes to enhance our understanding of prenatal influences on child development.